Features of the Brechtian educational curriculum in the presentations of students in the Art Education Department (Journal of the College of Basic Education, 2024)
The current research is based on an idea that the researcher derived from the educational curriculum founded by Brecht and employed it in constructing educational materials in dramatic formats in which the content and artistic form are linked through the dramatization of educational materials. Therefore, she defined the problem of her research with the following question:To what extent is it possible to employ the features of Brechtian theater in the performances of students in the Department of Art Education?To achieve the goal of the research, the researcher adopted the descriptive-analytical method in designing her procedures. She conducted a field survey of educational plays that follow Brecht’s theatre, and (4) plays emerged that formed a community for the current research. One sample was chosen, represented by (104 victims), which was subjected to analysis according to the indicators of the theoretical framework. To verify the research procedures, the researcher used the statistical package as follows: Cooper equation to extract the validity of the analysis tool. - Scott equation to calculate the stability of an analysis tool - Holsti correlation coefficient to correct the stability.The most important results are:1 - All the features of Brechtian theater appear in all the ideas of the dialogues (the text of the play).- Breaking the concept of the illusion of personification and making the actor (narrator) face the audience, speaking to them face to face through narration and setting direct questions for the recipient, as in ideas.